Data management in Nepalese medical sector: An empirical study - Singh, Priya (SADGAMAYA, 2024)
This study attempted to examine the influence of data management in the Nepalese medical sector and the impact of big data in health care. Many nations have strict policies and guidelines of data management of medical services. Countries with good ranking in health sector are the instances of this. Contemporary medical literatures have answered many issues, but the level of intensity or impact of unmanaged data in the medical sector and mechanisms to utilize EDI in the data management of the Nepalese medical sector are yet to be answered which is the quest of this article.